Analisis Kondisi Pasar Modal Pra Pasca Kenaikan BI 7-Day Repo Rate: Event Study Pada Perusahaan Sektor Properti dan Real Estate Yang Terdaftar di BEI - Gede Agus Indrawan; Luh Gede Kusuma Dewi (Universitas Pendidikan Ganesha, 2023)
This study aims to determine the condition of the capital market before the increase in the BI 7-Day (Reverse) Repo Rate in terms of the average differences in trading frequency, market capitalization, abnormal returns, and trading volume activity before and after events in property and real estate sector companies on the BEI. This research was conducted using the event-study method to assess the capital market's reaction to events. The type of data used in this study is secondary data with data collection techniques using the documentation method. Determination of the sample in this study was carried out by purposive sampling method with certain criteria so as to obtain a sample of 60 companies. The analysis technique used in this study is the Wilcoxon-Signed Rank Test with an observation period of 10 stock exchange working days. The results of the study show that: (1) there is no difference in the average trading frequency before and after the increase in the BI 7-Day Repo Rate. (2) there is a difference in the average market capitalization before and after the increase in the BI 7-Day Repo Rate. (3) there is no difference in the average abnormal return before and after the increase in the BI 7-Day Repo Rate. (4) there is no difference in average trading volume activity before and after the increase in the BI 7-Day Repo Rate.